Cleistes pallida (Orchidaceae Vanilloideae): a new species from South Brazil - Funez, Luís Adriano; Pansarin, Emerson Ricardo (Phytotaxa, 2018)
Cleistes pallida, a new species of Orchidaceae, is described and illustrated. The relationship of this new species to other taxa of the genus are discussed.